THE USE OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS' ABILITY IN WRITING A DESCRIPTIVE TEXT : A Quasi-Experimental Research at One Senior High School in West Bandung - Zahra, Retna Oktaviani (2013)
This research was aimed at investigating whether there is any improvement of students' writing ability in writing a descriptive text by the implementation of Jigsaw technique and discover students' response to the use of Jigsaw technique in teaching writing descriptive text. This research employed quantitative method in the forms of quasi-experimental design. This quantitative research involved two classes of tenth grade at one senior high school in West Bandung in which one class was assigned as the experimental group and the other one was assigned as the control group. The instruments used were pretest, posttest, and questionnaire of attitudes towards the Jigsaw technique. The posttest scores of the two groups were compared by using Independent t-test. The results showed the significance value was lower than the significance level which was 0.043 < 0.05. It meant that the Jigsaw technique improved students' ability in writing a descriptive text. Based on students' attitudes toward the use of Jigsaw technique, the findings indicated that most of students rated the used technique moderately positive. Nearly all of students agreed that Jigsaw technique is able to improve their writing skill, advance their grammatical mastery, increase their vocabulary mastery, expand their creative thinking, and improve their presentation skill as well as their confidence. Keywords: Jigsaw technique, cooperative learning, writing skill Penelitian ini bertujuan untuk menginvestigasi ada atau tidaknya peningkatan kemampuan menulis siswa dalam menulis deskriptif teks dengan menerapkan teknik Jigsaw dan untuk mengetahui respon siswa terhadap penggunaan teknik jigsaw dalam mengajar menulis deskriptif teks. Penelitian ini menggunaka metode kuantitatif dalam bentuk kuasi eksperimental desain. Penelitian kuantitatif ini melibatkan dua kelas dari kelas sepuluh di salah satu SMA di Bandung barat di mana satu kelas ditugaskan sebagai kelompok eksperimen dan yang lainnya ditugaskan sebagai kelompok kontrol. Instrumen yang digunakan adalah pretest, posttest, dan angket mengenai perilaku siswa terhadap teknik jigsaw. Nilai posttest dari kedua kelompok dibandingkan dengan menggunakan Independent t-test. Hasil penelitian menunjukkan nilai signifikansi lebih rendah daripada tingkat signifikansi yaitu 0,043 <0,05. Hasil penilitian ini menunjukan bahwa teknik Jigsaw meningkatkan kemampuan siswa dalam menulis teks deskriptif. Berdasarkan respon siswa terhadap penerapan teknik Jigsaw, temuan menunjukkan bahwa sebagian besar siswa menilai teknik yang digunakan cukup positif. Hampir seluruh siswa setuju bahwa teknik Jigsaw dapat meningkatkan kemampuan menulis, meningkatkan penguasaan tata bahasa, menambah penguasaan kosakata, memperluas pemikiran kreatif, meningkatkan keterampilan presentasi serta meningkatkan rasa kepercayaan diri siswa.